Answer:
-1
Step-by-step explanation:
First, we need to work out the left-hand side.
- find g(2) → g(2) = 2 - 1 which is 1
- next, find f(1) → f(1) = 1³ which is 1
Now, we can work out the right hand side.
- find f(-1) → f(-1) = -1³ which is -1
- then, find g(-1) → g(-1) = -1 - 1 = -2
Finally we can work out the full sum: 1 + -2 = -1.
Hope this helps!
Answer:
8 hours
Step-by-step explanation:
14 + 3x =38
-14 -14
--------------------
3x = 24
---- ----
3 3
--------------------
x = 8
Answer:
30
Step-by-step explanation:
45+45 = 90
150-90 = 60
60/2 = 30
I think...
Answer:
y=2/3x-1 is 3/2
y=-2/3x-1 is x=3/2
y=-3/2x-1 is x= 2/3
Step-by-step explanation:
Answer:
Step-by-step explanation: